KARAKTERISTIK AIR KOLAM PASCA TAMBANG BATUBARA YANG DIMANFAATKAN UNTUK BUDIDAYA PERAIRAN - Henny Pagoray; Ghitarina Ghitarina (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Utilization of after the coal mine pool for the cultivation need to know the quality,  so it can be known whether the appropriate media for fish life. The purpose of this study was to determine the characteristics of water quality of coal post-mining pool used for fish cultivation. The sampling method was in situ and ex situ, and then analyzed in the laboratory. The water were analyzed were temperature, pH, O2, NH3-N, NO3, NO2-N, PO4, -P, and H2S. Analysis of water quality compared to the quality of standard regulation of Province of Kalimantan Timur No. 02 / 2011 on Water Quality Management and Water Pollution Control. The results of the analysis showed that pH, NH3 and H2S exceed the quality standards.